MANAJEMEN PRODUKSI PROGRAM BURSA NIAGA DI RIAU TELEVISI - Delviza Septaningsih; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Competent television stations capture audience audiences by presenting programs that are certainly packed and presented as exciting as possible including the Exchange Bursa Niaga program. The intense competition in the packaging of this program makes the Bursa Niaga Business Strive to improve the content quality so that it can still attract the audience. For this reason this study aims to see how management includes planning, organizing, moving and supervision in the production of the program Bursa Niaga Trade in Riau Televisi. This research uses qualitative method with descriptive approach. The object of research is the production program management strategy of the Bursa Niaga which is produced by Riau Televisi. Research subjects consist of program producer, cameraman, program kabag, presenter determined by purposive method. Data collection techniques used were observation, in-depth interviews, and documentation. The results of this study describes how the application of planning, organizing, actuating, and controlling (POAC) in the production management of the program as an effort to produce quality programs. Bursa Niaga applies four stages: (1) planning (planning) carried out in three forms, namely content content planning meetings, financing planning meetings, facility planning and planning time aired. (2) organizing, Bursa Niaga has determined the distribution of each crew on duty onair or Bursa Niaga On The Spot with a specified work description. (3) Actuating (execution) of Bursa Niaga there are two onair and Bursa Niaga On The Spot. Onair begins with the determination of business topics, shooting, while On The Spot begins scriptwriting, taping, and post-production only for Bursa Niaga On The Spot which consists of making rundown events, editing process, and Bursa Niaga program display. (4) controlling conducted by Bursa Niaga shall be one of them in the projection and evaluation meeting. The whole set of processes is a form of management in the Bursa Niaga production process. Keywords: Management, Production Management Television, Television and Bursa Niaga